Mapping Research Trends in Digital Marketing and Electronic Word of Mouth in the Hospitality Industry: A Bibliometric Analysis - Bunga Indah Zaletri; Elida (Siber Journal of Advanced Multidisciplinary, 2026)
The rapid development of digital technology has transformed marketing strategies in the hospitality industry. Digital marketing and electronic word of mouth (e-WOM) have become widely discussed topics due to their influence on consumer perceptions and behavior. This study aims to map research trends in digital marketing and electronic word of mouth within the hospitality industry during the period 2015–2026. A bibliometric approach was employed using publication data retrieved from the Scopus database. A total of 35 relevant articles were analyzed using Bibliometrix and Biblioshiny to identify publication growth, leading sources, productive authors, highly cited documents, dominant keywords, and research topic trends. The findings reveal a significant increase in publications after 2020, with the highest number of publications recorded in 2025. The International Journal of Contemporary Hospitality Management and the Journal of Hospitality and Tourism Technology emerged as the most productive publication sources. Keyword analysis indicates that digital marketing, online reviews, social media, and electronic word of mouth are the most dominant research themes. Furthermore, recent studies have expanded toward topics such as artificial intelligence, big data, consumer trust, brand reputation, and customer satisfaction. The results suggest that research in this field has evolved from focusing on digital promotional tools to a broader understanding of consumer behavior and digital technologies in the hospitality industry. This study contributes to the literature by providing an overview of research developments and identifying opportunities for future research.